2017
DOI: 10.3390/su9071267
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear Relationship between Corporate Innovation and Environmental Sustainability

Abstract: This paper proposes and tests the impacts of firms' innovation activities, such as patents, on their involvement in environmental sustainability, such as environmental performance. Combining resource allocation and eco-innovation perspectives assuming constant levels of trade-off costs, this study proposes diminishing trade-off costs between corporate innovation and environmental sustainability. Specifically, this research hypothesizes a U-shaped relationship, suggesting that a firm will suffer trade-off costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…For example, McWilliams and Siegel [59] pointed out that a company's research and development activities and corporate social performance are positively correlated since many aspects of CSR create either product innovation, a process innovation, or both. Furthermore, following a few previous research results showing that both CSR and technology-related activities contribute to the intangible resources of the firms [58,60]. Similarly, Surroca, Tribó and Waddock [58] contend that companies could take advantage of CEP by employing activities and resources such as technological capability, the culture of the company, reputation, and human capital, which can strengthen firm performance [9].…”
Section: The Mediating Effect Of Technology Capabilitymentioning
confidence: 72%
“…For example, McWilliams and Siegel [59] pointed out that a company's research and development activities and corporate social performance are positively correlated since many aspects of CSR create either product innovation, a process innovation, or both. Furthermore, following a few previous research results showing that both CSR and technology-related activities contribute to the intangible resources of the firms [58,60]. Similarly, Surroca, Tribó and Waddock [58] contend that companies could take advantage of CEP by employing activities and resources such as technological capability, the culture of the company, reputation, and human capital, which can strengthen firm performance [9].…”
Section: The Mediating Effect Of Technology Capabilitymentioning
confidence: 72%
“…With reference to industry, we notice that most researchers have drawn on multi‐industries (e.g., Aboelmaged & Hashem, 2019; Palmer & Truong, 2017; Xing et al, 2019), with some taking a single industry perspective, mainly focusing on manufacturing (Chen & Liu, 2018; Stanovcic et al, 2015; Tariq et al, 2019) and on the service sector (Aboelmaged, 2018; Chang, 2018). As far as geographical region is concerned, most previous studies have focused on either developed (e.g., Lee & Kim, 2017; Saunila et al, 2018) or developing countries (e.g., Fernando et al, 2019; Zhang & Yang, 2016), while a variety of approaches is also observed in the measurement methods used (e.g., Chan et al, 2016; Li et al, 2017; Wu, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Sometimes, enterprises pursuing technological innovation can obtain contradictory results in environmental performance. Some authors affirmed that even the pursuit of environmental innovation could lead to undesirable results on environmental performance [9] because of the complexity of factors involved during the life cycle of the product. Therefore, it is necessary to analyze the relationship between environmental tools-such as CP-and broader environmental approaches, methods, and tools-such as life cycle assessment (LCA)-in order to make them more effective [10].…”
Section: Introductionmentioning
confidence: 99%